A Weaver's Memoir - Lenor Larson Jack (New York. : Harry N. Abrams, INC, 1998)
Contents
Chapter 1: The Early years
Chapter 2: Design
Chapter 3: Travels
Chapter 4: A Sense of Place
Chapter 5: On Collecting
Chapter 6: Mentors
Keywords: Men weavers--United States--Biography